Gossip-Based Data Distribution in Mobile Ad Hoc Networks - Miranda, Hugo (2009)
Wireless networks are useful in many different scenarios. They allow to create emergency networks for catastrophe response, wide area surveillance networks in hostile environments, or simply permit users to share information, play on-line games, and surf the Web. Mobile ad hoc networks are a particular case of wireless networks characterised by the absence of a supporting infrastructure.The thesis addresses the problem of building middleware services that permit to fully exploit the opportunities offered by mobile ad hoc networks. For that purpose, it is required to design algorithms that account for the limitations of mobile devices and that make a careful use of the scarce resources available in ad hoc networks. A central middleware service for mobile applications is data sharing. The thesis addresses the use of data replication as a technique to improve data availability and resource savings in mobile ad hoc networks. In particular, the thesis proposes the use of epidemic protocols to achieve these goals. In this context, the thesis presents the following contributions. It presents and evaluates $ı)$ an algorithm to reduce the number of transmissions required in a broadcast, $\ii)$ an algorithms for the geographical distribution of replicas of data items, and $\iii)$ algorithms to attenuate the impact of node movement in the geographical distribution. Finally, the thesis describes an application of the algorithms to build a concrete application, a version of the Session Initiation Protocol for wireless networks